Time management skills among medical students (Indian Journal of Public Health Research & Development, 2020)
Background: Time management is the art of arranging, organizing, scheduling and budgeting one’s timefor generating more effectiveness work and productivity. Effective time management techniques help us tojudiciously organise and plan time which we spend on various activities with the aim to increase productivityand quality of life. Students’ time is a limited resource. Time management plays a vital role in improvingstudent’s academic performance. So the present study was conducted to assess the time management skillsamong medical students and to find out correlation between time management and academic performance.Material and Methods: After taking informed consent, cross sectional study was conducted from July2018 to September 2018 among second year medical students. All medical students from second yearwilling to participate were included in the study (n= 115 students). The data was collected by using selfadministered close ended questionnaire. The questionnaire consisted of Time Management Questionnaire(TMQ) developed by Britton and Tesser (5 point Likert scale) with 18 questions. The data was analysed bypercentage, mean and Pearson’s correlation test. Results and conclusions: Mean score of time managementwas found to be 56.29±8.65 with maximum score of 81 and minimum score 36. A weak positive correlation(?=0.21) was found between time management score and academic performance. Sessions regarding timemanagement skills should be conducted for students.
Keywords: time management skills , academic performance, medical students